Too much equity - is there such a thing? The public discourse surrounding elective egg freezing subsidy in Israel - Daphna Birenbaum-Carmeli (BMC, 2023)
Abstract Background The preservation of human ova for future fertilization has been made available to healthy women in 2011-2012. This treatment, dubbed elective egg freezing (EEF), is undertaken primarily by highly educated unpartnered women without children, concerned of age-related fertility decline. In Israel, treatment is available to women aged 30-41. However, unlike many other fertility treatments, EEF is not state subsidized. The public discourse of EEF funding in Israel is the focus of the present study. Method The article analyzes three sources of data: press presentations of EEF; a Parliamentary Committee discussion dedicated to EEF funding; interviews with 36 Israeli women who have undertaken EEF. Results Numerous speakers raised the issue of equity, claiming that reproduction was a state interest and therefore, a state responsibility, including securing equitable treatment to Israeli women of all economic strata. Highlighting the generous funding of other fertility treatments, they claimed that EEF was inequitable, discriminating against poorer single women, who could not afford it. Few actors, however, rejected state funding as intervention in women's reproductive lives and called for reconsideration of the local reproductive imperative. Conclusion The invocation of equity by Israeli users of EEF, clinicians and some policy makers as grounds for a call to fund a treatment that serves a well-established subpopulation seeking to relieve a social rather than a medical problem, illustrates the profound context-embeddedness of notions of health equity. More generally, it may suggest that using an inclusive language in a discourse of equity may potentially be invoked so as to promote the interests of a particular subpopulation.